At The Age Of Preschool Education. Children Moral Education (Diversity Research: Journal of Analysis and Trends, 2024)
This article states that the task and content of moral education of children of preschool age requires the education and development of the child's spiritual world, his mind, moral feelings, and personal qualities. Education of moral feelings, ideas and behavior in children. Providing moral knowledge fulfills a number of educational tasks, we have given a broad vision and understanding of the moral values of human life and culture.